The Gionian essay put to the test of modernity: from deconstruction to aesthetic utopia - El Ouarrad, Ahmed (Romanica Olomucensia, 2023)
In his essays, Giono strives for an aesthetic view of the world. He considers that it is able to cure man of boredom and can remedy his psychic impasses. Art is in fact the reconciliation in man of his lower faculties (sensuality, instinct, and the body) and his higher faculties (common sense, which aims above all at a good life). Such a reconciliation requires a break with the universes created by science and technology and the ideology of progress which is consubstantial with it, because science and technology are the enemies of any aesthetic conception of the world. They curb man's sensuality, establish a relationship of domination between him and the cosmos, and cause him to tip over into a form of barbarism which is associated in Giono with the thought of the crowd which, itself, is generated by the thought of the concept. The latter is characterised above all by its utilitarian dimension and does not take into consideration either the joy of man or his freedom, because it imprisons him in what Nietzsche calls the common vision. Added to this is the fact that science and technology are breaking the link that man used to establish with the cosmos. And it is this rupture which constitutes, in the eyes of Giono, the misfortune of man.
Keywords: Giono; aesthetic utopia; modernity; revolt; art; technique; romanticism